Drip fertigation of water-soluble fertilizers: A tool to enhance nutrient and water use efficiency- A comprehensive review - Kaviyazhagan, S; Gurusamy, A; Subramanian, E; Prabhaharan, J; Amutha, R; Sivasankari, B; Arthirani, B; Rani, S; Dhayanethi, M (Plant Science Today, 2025)
Drip fertigation, which integrates drip irrigation with the application of water-soluble fertilizers, stands out as a highly efficient and sustainable agricultural technique. By delivering precise amounts of water and nutrients directly to the plant root zone, this method optimizes both water and nutrient use, significantly boosting crop yields while minimizing environmental impact. This is especially valuable in arid and semi-arid regions, where water scarcity and soil degradation are major concerns. One of the key benefits of drip fertigation is its ability to drastically reduce water wastage. The targeted delivery system minimizes evaporation, runoff and deep percolation losses, resulting in Water Use Efficiency (WUE) far superior to that of traditional irrigation methods. This is crucial for conserving limited water resources and ensuring the sustainability of agriculture in water-stressed areas. Additionally, the integration of fertilizers into the irrigation system enhances Nutrient Use Efficiency (NUE) by supplying nutrients in amounts closely matched to crop needs. This reduces losses from leaching and runoff, maintains soil fertility and lowers the risk of contaminating nearby water bodies. Drip fertigation also supports better crop growth and yield by providing controlled, stage-specific nutrition, which improves growth parameters such as plant height, leaf area and biomass. This leads to higher yields, improved crop quality and greater economic returns for farmers due to reduced input costs and increased productivity. Overall, drip fertigation not only conserves resources and supports food security but also promotes environmentally responsible and resilient farming practices.